“The guy who wrote Romeo and Juliet”: Shakespeare and Young Adult fiction (Altre Modernità, 2017)
For American teenagers, Shakespeare is much more than "the guy who wrote Romeo and Juliet", as Lena Haloway innocently defines him in the dystopian novel Delirium. In the US Shakespeare is still a constant fixture, "a mainstay in the curricula of America's schools and colleges, and the value of reading his work is still assumed" (Vaughan, Vaughan 2012:2); teenagers are required to engage not only with the works of the Bard but also with their modern adaptations at different stages of their education. The present paper investigates three American YA novels, published between 1999 and 2012, in which teenagers engage with Shakespeare's works. For the characters, reading is a formative experience that alleviates their pain, enables them to externalize their feelings, and to develop emotionally, psychologically and socially: texts are related to the lives of the young protagonists, questioned, challenged, moralized and used as a lens through which one can examine the teen world.